2020
DOI: 10.1111/jfpp.14818
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasound pre‐treatment and temperature on the quality and thermodynamic properties in the drying process of nectarine slices in a hot air dryer

Abstract: Drying is one of the ways to reduce postharvest waste and processing in agricultural products. Drying with hot air is one of the most popular drying methods in the food industry. The purpose of this study is to investigate the effect of ultrasound and temperature on the quality and thermodynamic properties in the process of drying nectarine slices in a hot air dryer. The drying process was performed at four levels of ultrasonic pre-treatment of 0 min (control sample), 10, 20, and 40 min and three temperature l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 50 publications
6
48
0
Order By: Relevance
“…These results are similar to those as reported by researchers for other agricultural products like pennyroyal, quince, almond and nectarine (Abbaspour-Gilandeh,Jahanbakhshi, Yeganeh, & Momeny, 2020;Kaveh, Jahanbakhshi, Abbaspour-Gilandeh, Taghinezhad, & Moghimi, 2018;Kaveh, Karami, & Jahanbakhshi, 2020).…”
supporting
confidence: 92%
“…These results are similar to those as reported by researchers for other agricultural products like pennyroyal, quince, almond and nectarine (Abbaspour-Gilandeh,Jahanbakhshi, Yeganeh, & Momeny, 2020;Kaveh, Jahanbakhshi, Abbaspour-Gilandeh, Taghinezhad, & Moghimi, 2018;Kaveh, Karami, & Jahanbakhshi, 2020).…”
supporting
confidence: 92%
“…All data were subjected to two‐way analysis of variance (ANOVA) in SAS 9.1. The mean values were separated by LSD (Least Significant Difference) test at p_0.05 (Jahanbakhshi et al., 2020). The p values of less than .05 considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the open sun drying method took 36% more time than the indirect type solar dryer for drying button mushroom. Jahanbakhshi, Kaveh, Taghinezhad, and Rasooli Sharabiani (2020) and Jahanbakhshi, Yeganeh, and Momeny (2020) studied the drying kinetics and the quality behavior of ultrasound pretreated pistachio samples under microwave dryer by varying microwave power range from 270 W to 630 W. It was found that the effective moisture diffusivity and specific energy of drying the ultrasound pretreated pistachio samples were varied from 1.4 to 4.3 × 10 −8 m 2 /s and 58–122.2kWh/kg, respectively. They further reported that the Adaptive Neuro‐Fuzzy inference system predicts the moisture ratio of dried ultrasound pretreated pistachio samples.…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that the best sensory acceptance and rehydration ratio was given by the samples, which were dried in a fluidized bed at 50°C. Jahanbakhshi, Kaveh, et al (2020) and Jahanbakhshi, Yeganeh, and Momeny (2020) designed and developed a hot air dryer for drying ultrasound pretreated nectarine samples at 50–75°C drying air temperature. It was observed that the Page model was fitted well with their experimental data.…”
Section: Introductionmentioning
confidence: 99%